Preparation And Characterization Of Hydrophobic Polyurethane Coating For Steel Surfaces - Soon, Li Jie (Universiti Sains Malaysia, 2022)
Hydrophobic surfaces are repellent to aqueous liquids and corrosive media. Polyurethane (PU) has hydrophobicity which are widely applicable in various fields. In this project, four different coating methods which were drop casting, spin coating, dip coating, and spray coating used to fabricate hydrophobic PU coating films on 304 steel plates. In addition, graphene nanoplatelets (GNP) was added in PU with 0.5% (w/v) to increase the properties of PU coating while stainless-steel 500 mesh was applied on coating surface to create high surface roughness of coating. Then the coatings were characterized through FTIR, XRD, AFM, and WCA measurement as well as mechanical test such as tensile test and corrosion resistance test. The WCA measurement of coating after incorporation of GNP into PU showed the increasement about 12.04°-23.09°. GNP also successfully decreased the corrosion rate of coating in 3.5 % NaCl solution by blocking the corrosive ion from entering the gaps and pores in PU. The mechanical strength of film increased with the existence of strong hydrogen bond within the film. The application of stainless-steel 500 mesh improved the surface roughness of coatings also help in increasing the WCA of 5-8°, air trapped in between coating and surrounding environment protect the coating surface with low surface energy. The application of stainless-steel 500 mesh can further decrease the corrosion rate of 304 steel. This study provides a comprehensive comparison of PU, PU-mesh, PU/GNP, and PU/GNP-mesh coatings surface morphologies, hydrophobicity, and corrosion resistance properties.